If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + -19) * 2 = 4 Reorder the terms: (-19 + x) * 2 = 4 Reorder the terms for easier multiplication: 2(-19 + x) = 4 (-19 * 2 + x * 2) = 4 (-38 + 2x) = 4 Solving -38 + 2x = 4 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '38' to each side of the equation. -38 + 38 + 2x = 4 + 38 Combine like terms: -38 + 38 = 0 0 + 2x = 4 + 38 2x = 4 + 38 Combine like terms: 4 + 38 = 42 2x = 42 Divide each side by '2'. x = 21 Simplifying x = 21
| 4(5q-4)-[2(3q-3)+5]= | | x+-3=-1 | | (x-8)(x-8)=49 | | 8*(x-2)+16=6*(x-2) | | x^2+12=72 | | x-(-9.9)=2.1 | | 6-5(3x-3)=-39 | | x+7.1=3.9 | | 9x+56=16x+10 | | 8*(x-2)+16=24/8 | | 3x-8=26 | | 8*(x-2)+16=24 | | 3(y+3)-8y=24 | | 3(n-9)-(1-n)= | | x^3-x^2-9x+9=0 | | x-3.1=4.1 | | 275=18-x | | 4b^2+5b^2-2b^2-5b^2= | | 3x-6x=5 | | x-9.9=7.9 | | 4x+50+x+43=180 | | 4x+x+43=180 | | x-5.1=3.1 | | 7*(x+3)+10=21 | | 6x+6x=16-4x | | 6x+6x=16-4 | | 2(w+7)=-2w+42 | | x+3.1=9.1 | | 101-3x=3x+11 | | 3x-17=-27 | | 7*(x+2)=21 | | x+4.9=6.1 |